Constraint of Paud Teacher’s Innovativeness - Henny Suharyati (STKIP Singkawang, 2016)
The purpose of this reasearch is to study the constraint of Paud teacher’s innovativeness by examining the threevariables which will become the strongest aspect to increase Paud teacher’s innovativeness such as organization culture, transformational leadership and job motivation. The survey is conducted by taking sample of 144 teachers who had been graduated from The Teachers Training College by proportional random sampling technique at Paud teachers in Bogor, west Java, Indonesia. The research used a Sequential Explanatory Design Mixed Method. The quantitative research is firstly conducted then followed by the qualitative research to support the research more comprehensively understood.The quantitative research portrays that there is a very significant positive correlation between those three variables strengthening the Paud teacher’s innovativeness. This relationship is also supported by the qualitative research which organizational culture, transformational leadership and job motivation give higher scores to support Paud teacher’s innovativeness